Applying Digital Twins to Research the Relationship Between Urban Expansion and Vegetation Coverage: A Case Study of Natural Preserve - Zhao, Dongmiao; Li, Xuefei; Wang, Xingtian; Shen, Xiang; Gao, Weijun (Frontiers in Plant Science, 2022)
With the growth of world population, cities expand and encroach on forests and plants, caused many environmental problems. Digital Twin, as the rapidly developing technique in recent years, provides the opportunity to implement the specific situation of forests and plants on present or in the future, which has great performance on predictive analysis and optimization. From the consideration of plants and forests, this paper provides a comprehensive case study to research the relationship between urban development boundary and natural environment in a natural preserve in a coastal city. Multispectral data of the study area is collected by Unmanned Aerial Vehicle (UAV), combining Satellite remote sensing historical data and geographic data to establish the digital twin model for plant identification. In conjunction with local Master planning of land use, the results of modelling is used to analyze the influences of urban construction on natural environment, and the inappropriate aspects of the planning are discovered and summarized. In addition, 6 suggestions to the effective management and planning strategies are presented. As plants and forest are effective factors of natural conditions, this study offered an objective assessment for the sustainability and rationality of urban planning with some guidance and bases.